The Analysis of Parallelism in Joe Biden’s Speech and Its Application in Teaching Speaking - Sasti Febianti; Sri Widodo; Juita Triana (Scripta : English Department Journal, 2022)
This research aims to find out the type of parallelism Joe Biden speech in the national democratic convention and to describe the application in teaching speaking. The research methods are descriptive qualitative. The data source is Joe Biden’s speech transcript. The research subject is parallelism in the form of words, phrases and utterances. The research instrument is the researcher herself. The result shows that there are 10 types of parallelism; in detail, lexical parallelism: 2 data of epanalepsis (4%), 29 data of anaphora (55%), 3 data of medial (5%), 3 data of epistrophe (5%), and 1 data of anadiplosis (2%); syntactic parallelism: 5 data of sentence parallelism (9%), 1 data of phrase parallelism (2%), and 7 data of word parallelism (13%); semantic parallelism: 2 data of antithesis (4%); and phonological parallelism: 1 data of assonance (2%). The application of the parallelism found from the script in teaching speaking can be applied in grade XII of senior high school.